Organizations and Management - Brady, David (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Welcome to S155: Organizations and Management! Sociologists have long documented that social life involves interacting with and being a member in a host of organizations – churches, workplaces, universities, governments and communities. Throughout the semester, we will seek to understand the way organizations work, why organizations frustrate, empower and enable people, and how organizations reflect and shape society. This course is NOT a "how-to" course or a practical cookbook on management. Instead, the course is focused on integrating theory and practice. In the process, we will enrich our understanding of the "real world" with greater analytical and theoretical depth, and rigorous comparisons of different organizations. This course is both as a core course in Duke’s Markets and Management Certificate, and an upper-level Sociology of Organizations and Management. While our class will hopefully cultivate a sociological imagination towards organizations, we will engage multiple social science disciplines, the business literature, and public policy debates. My main aspiration is that students leave the course with a thoroughly sophisticated understanding of the social dynamics of organizations and management. Further, I hope students are able to apply the knowledge they have gained to the organizational experiences in their past, present and future lives, careers and citizenship.